2008
DOI: 10.1128/aem.00594-08
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Extracellular and Intracellular Proteomes ofListeria monocytogenesStrains Reveals a Correlation between Protein Expression and Serovar

Abstract: Listeria monocytogenes, the etiologic agent of listeriosis, remains a serious public health concern, with its frequent occurrence in food environments coupled with a high mortality rate. Among the 13 serovars, human listeriosis is mostly associated with the serovar 4b, 1/2b, and 1/2a strains. To investigate the diversity of L. monocytogenes, the intracellular and extracellular proteins of 12 strains were analyzed by two-dimensional gel electrophoresis. These strains had different origins, belonged to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 42 publications
(34 reference statements)
0
26
0
Order By: Relevance
“…This study not only identified genes that differed between strains with regard to B dependence of their transcription, but also found that B contributed significantly to acid and oxidative stress survival and Caco-2 cell invasion in lineage I, II, and III strains, but not in the lineage IV strain (Oliver et al, 2010). A proteomics study comparing strains from serotypes 1/2a (lineage II), 1/2b, and 4b (lineage I) found 26 proteins overexpressed in 1/2a strains as compared to the other strains while 20 other proteins were underexpressed in the 1/2a strains (Dumas et al, 2008), further supporting that L. monocytogenes lineages differ in their gene expression patterns. Overall, most differences in gene expression between lineages I and II strains found so far are associated with stress response regulation.…”
Section: Differences In Gene Expression Between Lineagesmentioning
confidence: 94%
“…This study not only identified genes that differed between strains with regard to B dependence of their transcription, but also found that B contributed significantly to acid and oxidative stress survival and Caco-2 cell invasion in lineage I, II, and III strains, but not in the lineage IV strain (Oliver et al, 2010). A proteomics study comparing strains from serotypes 1/2a (lineage II), 1/2b, and 4b (lineage I) found 26 proteins overexpressed in 1/2a strains as compared to the other strains while 20 other proteins were underexpressed in the 1/2a strains (Dumas et al, 2008), further supporting that L. monocytogenes lineages differ in their gene expression patterns. Overall, most differences in gene expression between lineages I and II strains found so far are associated with stress response regulation.…”
Section: Differences In Gene Expression Between Lineagesmentioning
confidence: 94%
“…The differences in reactivity observed between lineages may also be attributed to differential expression of LMOf2365_0639 between lineages. A proteomic study of several L. monocytogenes isolates of various serotypes reported that total surface protein patterns of isolates can be grouped by lineage classification (35). In addition, while the epitope recognized by M3643 is identical between sequenced L. monocytogenes isolates and other Listeria species isolates, M3643 was highly specific to L. monocytogenes cultured in BHI.…”
Section: Discussionmentioning
confidence: 99%
“…The same effect has been verified by other authors. Dumas et al (15) stated that PlcB and InlC from L. monocytogenes were present in five and four spots, respectively, with different pIs and relative molecular weights (M r s). These authors explained this effect by the possible presence of protein orthologues with different M r s, pIs, and/or posttranslational modifications (isoforms).…”
Section: Discussionmentioning
confidence: 99%